Development and sensory evaluation of added bread from soursop residue flour (Research, Society and Development, 2020)
Bread is a product widely consumed since ancient times, so many scholars seek to create new formulations that give them more flavor and nutritional quality through the full reuse of food. Soursop is rich in minerals such as calcium, potassium, magnesium and vitamins (A, B and C). Thus, the objective was to elaborate loaves of bread added with different concentrations of soursop residue flour, as well as to evaluate the sensory characteristics of the elaborated products. Initially the soursop peels were dried in a 60 ° C circulating oven for 24 hours and then flour was obtained. Then different formulations of loaves of bread were prepared: PFC (0% soursop residue flour), PF10% (10% soursop residue flour) and PF20% (20% soursop residue flour). Sensory analysis was performed using the affective test with a nine-point structured hedonic scale and the purchase intention test. From the results, it was inferred that in the sensory analysis, the PFC sample had an acceptability higher than 80% for all evaluated attributes, while the PF10% bread had an acceptability index higher than 73% and the PF20% bread reached acceptability index. over 66% for all appreciated attributes. Therefore, it was found that it is possible to partially replace wheat flour with soursop residue flour in the production of loaf breads, since PF10% was not affected by the addition of flour.